Pharmacokinetic Analysis of Melphalan after Superselective Ophthalmic Artery Infusion in Preclinical Models and Retinoblastoma Patients - Schaiquevich, Paula Susana (2012)
Purpose: To characterize melphalan pharmacokinetics after super-selective ophthalmic artery infusion (SSOAI) in animals and children with retinoblastoma. Methods: Vitreous and plasma samples of 5 Landrace pigs were obtained over a 4-hour period after SSOAI of melphalan (7 mg). Melphalan 50 % inhibitory concentration (IC50) was evaluated in retinoblastoma cell lines. Plasma samples were obtained from 17 retinoblastoma patients after SSOAI of 3 to 6 mg of melphalan to one (n=14) or two eyes (n=3). Correlation between plasma pharmacokinetics and age, dosage and systemic toxicity was studied in patients. Results: In animals, melphalan peak vitreous levels were greater than its IC50 and resulted in 3-fold vitreous-to-plasma exposure. In patients, large variability in pharmacokinetic parameters was observed and it was explained mainly by body weight (p< 0.05). A significantly higher systemic area under the curve was obtained in children receiving more than 0.48 mg/kg for bilateral tandem infusions (p< 0.05). These children had 50 % probability of grade 3-4 neutropenia. Plasma concentrations after 2 and 4 hours of SSOAI were significantly higher in these children (p< 0.05). A synergistic cytotoxic effect of melphalan and topotecan was evident in cell lines (p<0.001). Conclusions. Potentially active levels of melphalan after SSOAI were achieved in the vitreous of animals. Low systemic exposure was found in animals and children. Doses greater than 0.48 mg/kg, given for bilateral tandem infusions, were associated with significantly higher plasma levels and increased risk of neutropenia. Synergistic in vitro cytotoxicity between melphalan and topotecan favors combination treatment.